1992
DOI: 10.1136/gut.33.7.933
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine production in patients with inflammatory bowel disease.

Abstract: The production of cytokines in peripheral blood mononuclear leukocytes of patients with inflammatory bowel disease was investigated. T cell subset analysis and differential white blood cell counts were also performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 12 publications
5
69
0
Order By: Relevance
“…It has been proposed that the cytokine-induced increase in intestinal TJ permeability represents an important proinflammatory mechanism (14,26). The cytokine-induced increase in intestinal TJ permeability allows increased paracellular permeation of luminal Ags, bacteria, and other toxic substances that promote inflammation (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the cytokine-induced increase in intestinal TJ permeability represents an important proinflammatory mechanism (14,26). The cytokine-induced increase in intestinal TJ permeability allows increased paracellular permeation of luminal Ags, bacteria, and other toxic substances that promote inflammation (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in Crohn's disease showed that mononuclear cells and macrophages isolated from the lamina propria expressed high levels of TNF-␣ (6, 41) and IL-1␤ (24,30,32). Inflamed colonic mucosa obtained from patients with active Crohn's disease spontaneously produced increased amounts of TNF-␣, IL-6, and IL-1␤ compared with normal mucosa (8,21,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The proteins encoded by the IL-1 a and IL-1/3 genes appear to play an important role in chronic IBD, since enhanced production of IL-1 has been reported in gut tissue of animal models of intestinal inflammation [13,14], as well as in the mucosa [15] and isolated cell preparations of patients with active IBD [16,17].…”
Section: Introductionmentioning
confidence: 99%